Characteristics of squid (Illex illecebrosus LeSueur) fillets dried using a combination of heat pump drying and far infrared radiation. - Qian, Bingjun; Deng, Yun; Wu, Juan; Su, Shuqiang; Feng, Xiaoxia (2011)
Squid (Illex illecebrosus LeSueur) fillets were dried using a heat pump (HP) dryer combined with far infrared radiation (FIR) at 500, 1000 and 2000 W. Squids with an initial moisture content of 83.73+or-0.39% (w.b.) were dried to about 17% (w.b.) at 50 degrees C and at an air flow rate of 0.8 m s-1. The drying data were fitted to 11 thin-layer drying models, among which the Page model gave better predictions than the others. The effective moisture diffusivity calculated from the second Fick's law increased from 0.53x10-10 to 1.33x10-10 m2 s-1, with an increase in FIR intensity, which suggested that FIR contributed to moisture loss and thus decreased drying time. Changes in hardness and color increased with an increase in the power supplied to FIR. No significant differences in shrinkage were found for all dried samples. HP+FIR with 500 W gave the highest rehydration rate compared with the other drying methods.
Keywords: Squids; Heat pumps